Anti-proliferation activities of Oryza sativa L. anthocyanins-Hohenbuehelia serotina polysaccharides complex after in vitro gastrointestinal digestion. (January 2020) - Wang, Lu; Zhou, Peng; Feng, Ru; Luo, Zhen; Li, Xiaoyu; Gao, Lili
Abstract: In order to improve the bioavailability of Oryza sativa L. anthocyanins, we fabricated Oryza sativa L. anthocyanins- Hohenbuehelia serotina polysaccharides (OSA-HSP) complex and investigated its anti-proliferation activities taking into account its changes along simulated gastrointestinal digestion in vitro . Results showed that OSA mainly composed by delphinidin, cyanidin, petunidin, malvidin and their derivatives was combined with HSP through electrostatic interaction. OSA-HSP complex belonged to non-crystalline substance, and had compact and laminar structural characteristics. Under simulated gastrointestinal digestion, OSA-HSP complex significantly prevented the degradation of anthocyanins, and presented sustain release effect. However, the anti-proliferation activities of OSA-HSP complex digested by different gastrointestinal process were remarkably changed, especially after small intestinal digestion. HeLa cells treated with OSA-HSP complex exhibited pro-apoptosis characteristics by triggering endogenous mitochondrial apoptosis pathway through activating the expressions of Bax, cytochrome c and Caspase-3 as well as inhibiting the expression of Bcl-2. These findings provided new insight to improve the bioavailability of anthocyanins in functional foods and tumor therapy. Highlights: OSA-HSP complex was innovatively fabricated and characterized. The sustain release characteristics of OSA-HSP complex were elucidated. The antiproliferation activity of OSA-HSP complex during digestion was measured. The anti-proliferative mechanism of OSA-HSP complex was systemically revealed.